Modal Analysis and Optimization of Tractor Exhaust System - Ayla Tekin; Halil Şamlı (Applied Sciences)
Excessive vibrations in exhaust systems can significantly reduce a vehicle’s lifespan and compromise performance. These vibrations, caused by factors such as engine operation and road conditions, lead to wear and tear. To address this issue, a finite element analysis (FEA) was conducted on a 90-horsepower tractor’s exhaust system. Using ANSYS WB®, a 3D model was created and modal analysis was performed to determine the system’s natural frequencies and mode shapes. Based on the results, geometric modifications were made to the exhaust system, increasing its stiffness and shifting vibration frequencies to higher values. Consequently, vibration levels, noise, and the risk of component failure were significantly reduced. The redesigned exhaust system was successfully implemented in production. This study demonstrates the effectiveness of FEA in analyzing exhaust system vibrations and facilitating design improvements. By extending vehicle lifespan and providing a quieter, more comfortable driving experience, this research offers valuable insights for automotive and mechanical engineers.